1983
DOI: 10.1088/0031-9155/28/9/003
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the presence of secondary electrons in megavoltage photon beams (radiotherapy application)

Abstract: The presence of secondary electrons in photon beams of 60Co and 4, 8, 10, 15 and 25 MV x-rays has been studied by measuring surface charge using thin window ionisation chambers. Measurements have been made for square fields from 4 X 4 cm2 to 35 X 35 cm2 for locations from the collimator head to a distance of 4 m from the target. In addition, measurements have been made for rectangular fields at 10 MV and 25 MV for fields of equivalent area from 5 X 5 cm2 to 25 X 25 cm2. By eliminating the inverse square effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 7 publications
5
38
0
Order By: Relevance
“…The Sc is caused by (i) source obscuring, (ii) head scattering, (iii) monitor chamber back scattering. The type of phantom and depth of measurement are the topics of interest and it has been reported by several authors [1,2,6,12,13,14,17,16,19]. The ESTRO has recommended a columnar mini phantom for the measurement of Head Scatter Factor [5].…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sc is caused by (i) source obscuring, (ii) head scattering, (iii) monitor chamber back scattering. The type of phantom and depth of measurement are the topics of interest and it has been reported by several authors [1,2,6,12,13,14,17,16,19]. The ESTRO has recommended a columnar mini phantom for the measurement of Head Scatter Factor [5].…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…Hence the direct measurement of S C is usually done as an in-air measurement with an ion chamber covered with a build-up cap. A number of studies has been reported in the literature Biggs P. J. et al [1,2], Mackie T. R. [14], Luxton G. [12,13], Tatcher M.…”
Section: Introduction Introduction Introductionmentioning
confidence: 99%
“…X-ray beams are used to deposit absorbed dose at depth within a patient at the site of the tumour. High energy x-rays produce a skin sparing effect whereby more dose is deposited at depth than in the skin tissue region [1][2][3][4] . This effect is due to longitudinal disequilibria of electrons excited by the high energy x-rays.…”
Section: Introductionmentioning
confidence: 99%
“…39 The type of phantom and depth of measurement of Sc values are topics of interest, as has been reported by several authors. 4,7,9,14,29,32 The AAPM therapy physics committee Task Group 74 (TG-74) 13 recommends the build-up caps in cylindrical shapes along with long axis parallel with beam central axis and the ion chamber placed at 10 g/cm 2 water equivalent depth for head scatter factor measurements. The present study emphasizes the need for Sc measurements at 10 cm water equivalent depth with mini phantom for 6MV-FB photon beams.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those found by Henkelom et al, 45 Zhu et al, 13 Ling and Biggs. 28,29 The collimator exchange effect was studied for both 6MV-FB and 7MV-UFB photon beams produced in Varian (Clinac iX (2300CD)) and Siemens (Artiste) as shown in Figs. 9 and 10 and Table 2.…”
Section: Fig 5 -Variation Of Sc With Field Size For Different Ssd Fomentioning
confidence: 99%